Waste in Mukbang Events from Ibnu Ajibah's Perspective (Character Study of the Verses "Israf") - Umi Hani Khofifah; Ikhwanudin Ikhwanudin; Muhammad Nur Amin (al-Afkar, Journal For Islamic Studies, 2026)
The Mukbang phenomenon digital content featuring the act of eating large portions has grown increasingly popular on social media and sparked a discourse on consumption ethics within digital culture. This study aims to analyze wasteful practices in Mukbang shows through the lens of Ibn Ajibah’s thought on the concept of “israf” (excess) in Islamic consumption ethics. This study employs a qualitative method using a literature review approach, analyzing the works of Ibn Ajibah, secondary sources on Mukbang, and several examples of Mukbang content analyzed descriptively. This study uses Quranic verses Al-A’raf 31, Al-An’am 141, and Surah Thaha 81 as objects of interpretation regarding the values of “israf”. The results indicate that, according to Ibn Ajibah’s perspective, excessive consumption not based on need or public welfare constitutes wastefulness and poses potential health risks. Furthermore, this study contributes to the development of Islamic consumption ethics in Qur’anic exegesis and emphasizes the importance of re-examining popular consumption practices to ensure they align with Qur’anic values and social responsibility in Islam.